USER SATISFACTION AND FUTURE INTENTION IN THE INDONESIAN SHARING ECONOMY: EMPIRICAL INSIGHTS - Grace Carolina Malau (Journal of Economics Education and Entrepreneurship, 2026)
The rapid expansion of the digital sharing economy in Indonesia has intensified competition among ride-hailing platforms, making long-term user retention increasingly critical. In this context, this study investigates the critical determinants of Future Intention among users of Gojek, specifically examining the mediating roles of Sustainability and User Satisfaction in the relationship between Economic Benefit and Future Intention. The research provides insights into how the platform can strategically manage its economic success to secure long-term user retention. A quantitative empirical approach was employed, with primary data collected through an online survey disseminated via social media. The target population consisted of ride-hailing users in Indonesia's three largest cities: Jakarta, Surabaya, and Medan. Using purposive and snowball sampling techniques, 497 eligible users who had used the service for at least six months were recruited. The findings confirm that Economic Benefit strongly and positively influences Sustainability and User Satisfaction, both of which significantly drive Future Intention. Mediation analysis reveals that Sustainability exerts a stronger mediating effect than User Satisfaction. Theoretically, sustainability functions as a value-enhancing mechanism transforming short-term economic benefits into long-term loyalty. Practically, platforms should integrate economic efficiencies through a sustainability lens to maintain competitive advantage.